2016
DOI: 10.1097/eja.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of platelet supplementation for the reversal of ticagrelor-induced inhibition of platelet aggregation

Abstract: Platelet supplementation restored platelet aggregation in aspirin-spiked but not in ticagrelor-spiked samples. These results do not support the use of platelet transfusion to reverse the effects of ticagrelor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 24 publications
4
37
0
1
Order By: Relevance
“…If bleeding occurs during surgery, platelet transfusion has been shown to effectively counteract ASA effects. [166][167][168] This finding further supports the possibility of continuing ASA throughout the perisurgical period as ASA allows direct antiplatelet effect reversal if clinically indicated. The increased risk of bleeding complications if ASA and other antithrombotic drugs are not discontinued should be weighed against the potentially increased risk of thrombotic complications during the pre-operative cessation period.…”
Section: 157supporting
confidence: 53%
“…If bleeding occurs during surgery, platelet transfusion has been shown to effectively counteract ASA effects. [166][167][168] This finding further supports the possibility of continuing ASA throughout the perisurgical period as ASA allows direct antiplatelet effect reversal if clinically indicated. The increased risk of bleeding complications if ASA and other antithrombotic drugs are not discontinued should be weighed against the potentially increased risk of thrombotic complications during the pre-operative cessation period.…”
Section: 157supporting
confidence: 53%
“…10 The possibility of normalizing platelet reactivity after ticagrelor therapy has also been investigated in a few small studies with mixed outcomes, ranging from no recovery at all, 11, 12 to some restoration of function. 13 Clopidogrel and prasugrel are members of thienopyridine class, binding irreversibly to the P2Y 12 receptor and exerting long acting inhibitory effects, whereas ticagrelor is the first member of the cyclo-pentyl-triazolo-pyrimidine class, with reversible binding and short-acting effects, hence the twice-daily administration.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors observed a partial restoration of platelet aggregation in patients on maintenance treatment with these drugs, other studies and case reports provided conflicting data. 6,7,[9][10][11] The complete inefficacy of platelet transfusions to reverse the antiplatelet action of ticagrelor was nicely highlighted in a case report of a patient with intracranial hemorrhage, where platelet reactivity levels remained virtually unchanged despite transfusion of 17 U of platelets. 7 Other reports provided similar results.…”
Section: Sibbing and Massberg Restoring Platelet Function On Antiplatmentioning
confidence: 99%
“…As long as this is not the case, we have to take the data coming from (in vitro) studies such as APTITUDE 5 and others [6][7][8][9][10] as the best available evidence for guidance of patient treatment. Second, the comparatively low sample size for prasugrel-treated patients (n=6) and ticagrelor-treated patients (n=3) in the APTITUDE-CABG cohort precludes from drawing definite conclusions on the feasibility of immediate and sustained platelet restoration after platelet transfusion with these 2 agents.…”
Section: Sibbing and Massberg Restoring Platelet Function On Antiplatmentioning
confidence: 99%
See 1 more Smart Citation